TRAKTOR CULTIVATOR MINI UNTUK GABUNGAN KELOMPOK TANI (GAPOKTAN) LIMBUNG INDOMAKMUR - Junaidi . (Universitas Muhammadiyah Pontianak, 2018)
ABSTRACTThe Limbung Indomakmur Farmer Group is a Horticultural Farmer Group located in Limbung Village, Sungai Raya Sub-district, Kubu Raya District. Problems faced by farmers are related to land processing. The land processing done so far is still using simple agricultural equipment, Farmers need a long time due to uneven land contours. Farmers do not have adequate equipment and technology to process the land. Through PKM activities were given a modified Culvivator Mini Tractor Machine according to conditions in the field. With this machine can shorten the processing time of the land. Keywords: Association of Farmers' Groups, Land Processing, Mini Cultivator Tractors